'"A very, very bad mood": the turn to horror in Alan Moore's late comics'. Issue 1 (2nd January 2023) - Ayres, Jackson
ABSTRACT: This essay attends to the 'turn to horror' that ends Alan Moore's career as a comic book writer, focusing on his trilogy of miniseries inspired by the fiction of H.P. Lovecraft. After tracing the ways in which Moore's Lovecraft comics employ techniques found in his revisionist superhero comics from the 1980s, the essay argues that Moore's horror comics also revisit a political critique from his early superhero work. Attention to Moore's turn to horror clarifies the shape of his career.